2023
DOI: 10.3390/cells12111497
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Released by Genetically Modified Macrophages Activate Autophagy and Produce Potent Neuroprotection in Mouse Model of Lysosomal Storage Disorder, Batten Disease

Abstract: Over the recent decades, the use of extracellular vesicles (EVs) has attracted considerable attention. Herein, we report the development of a novel EV-based drug delivery system for the transport of the lysosomal enzyme tripeptidyl peptidase-1 (TPP1) to treat Batten disease (BD). Endogenous loading of macrophage-derived EVs was achieved through transfection of parent cells with TPP1-encoding pDNA. More than 20% ID/g was detected in the brain following a single intrathecal injection of EVs in a mouse model of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In the same context, a recent article published suggested that sEV derived from macrophages transfected with the lysosomal enzyme tripeptidyl peptidase-1 (TPP1), an enzyme used as a target for treating Batten disease (BD, a pathology that affects the nervous system in children), could be used as an alternative cure for this pathology. Being a disease that affects the nervous system, the administration of a localized drug is not easy, and in this case, the authors were able to administer TPP1 effectively and cumulatively through sEV via intrathecal and intraperitoneal routes in the BD mouse model, observing a significant therapeutic effect [ 51 ]. These results demonstrate the positive therapeutic effects that can be harnessed from macrophages, cells that cross the BBB and could deliver these sEV loaded with therapeutic agents.…”
Section: Antigen Presenting Cellsmentioning
confidence: 99%
“…In the same context, a recent article published suggested that sEV derived from macrophages transfected with the lysosomal enzyme tripeptidyl peptidase-1 (TPP1), an enzyme used as a target for treating Batten disease (BD, a pathology that affects the nervous system in children), could be used as an alternative cure for this pathology. Being a disease that affects the nervous system, the administration of a localized drug is not easy, and in this case, the authors were able to administer TPP1 effectively and cumulatively through sEV via intrathecal and intraperitoneal routes in the BD mouse model, observing a significant therapeutic effect [ 51 ]. These results demonstrate the positive therapeutic effects that can be harnessed from macrophages, cells that cross the BBB and could deliver these sEV loaded with therapeutic agents.…”
Section: Antigen Presenting Cellsmentioning
confidence: 99%